(3GdJbjjO deYQaI QhGI GdSff hGdeSGfjOs - (3GHf ofbWI GdMfHdj GdHZOGOj , eMeO Hf YHO GdZfj Hf CHj HcQ Hf TLGY, eYjf GdOjf, GHf ofbWI , CHh HcQ J (B629 (3g` s
(3ChdgG (B:s
(3CeG HYO , aEfg SCdfi GdTjN GdbQWHi Cf CLeY LRAkG jTJed Ydi eYQaI QhGjI GdcJH GdSJI (B: (3cJGH UMjM GdHNGQi hbGd di CMH Cf CYQa CNHGQge hLQMge hJYOjdge s
(3BNQgG (B:s
(3JQLeI TgOI HfJ CMeO Hf GdaQL GdEHQi , aNQ GdfSGA SeYJ ef CHj GdNWGH fUQ Hf CMeO hdgG QhGjI ai eSfO MOK YfgG GdMaGX CHh GdaQL GdLhRi hSeGYgG UMjM JhajJ ai KGdK YTQ eMQe SfI CQHY hSHYjf hNeS eFI , hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3fSNI fajSI ef cJH GdEeGe jMji MejO GdOjf ai UfYGA cJHJ Hbde eged GdfbW CMjGfkGs
(3HChdgG JedcGJ CbOegG (B1229 (3g`s
(3UhQJ Yf fSNI GdEeGe jMji (B_ (3UfYGA s
(3ai GdeYgO fSNJGf CNQjGf Qbe (B186 (3JGQjN hKGdKI Qbe (B1519 (3JGQjN ecQQI Yf GdKGfjI s
(3bQf GdfSN (B:s
Keywords: (3GdJGQjNs